Impact of Amanah Ikhtiar Malaysia's microcredit programs on women empowerment in northern corridor economic region - Mohd Saad, Nariman; Ali, Jamal; Kamarudin, Roslina (2013)
Women's empowerment refers to gender equality. Promotes participation of women in all levels of development planning and practice. In Malaysia, the public sector plays an important role in enhancing women empowerment such as the Amanah Ikhtiar Malaysia program under the Malaysian Islamic Economic Development Foundation (Yayasan Pembangunan Ekonomi Islam Malaysia, YAPEIM). AIM program is specifically to encourage poor women involved in small business. AIM will assists and monitors them to ensure the success of their business.This can increase income and in turn eradicate poverty among women.Thus, increase empowerment of women.This paper therefore examines the impact of AIM program on the welfare of women who received AIM’s microcredit assistance and engaged small businesses in the Northern Corridor Economic Region - Perlis, Kedah, Penang and northern Perak. The study employs Structural Equation Method (SEM) to assess the impact of AIM’s micro-credit assistance among the participants. A total of 1,000 participants were randomly selected and interviewed. The results showed that the AIM’s micro credit assistance program for the targeted group has increased their economic well-being.